Effectiveness of Robot-Assisted Upper Limb Training on Spasticity, Function and Muscle Activity in Chronic Stroke Patients Treated With Botulinum Toxin: A Randomized Single-Blinded Controlled Trial - Gandolfi, Marialuisa; Valè, Nicola; Dimitrova, Eleonora Kirilova; Mazzoleni, Stefano; Battini, Elena; Filippetti, Mirko; Picelli, Alessandro; Santamato, Andrea; Gravina, Michele; Saltuari, Leopold; Smania, Nicola (Frontiers in Neurology, 2019)
Background: Upper limb (UL) spasticity and weakness are tightly intertwined in the spastic movement disorders. The combined use of Robot-assisted UL training and Botulinum toxin (BoNT) appear to be a promising therapeutic synergism to improve UL function in chronic stroke patients. Objective: To evaluate the synergistic effects of Robot-assisted UL training and Botulinum toxin on UL spasticity, function, muscle strength and the electromyographic UL muscles activity. Methods: This single-blind, randomised, controlled trial involved 32 chronic stroke outpatients with UL spastic hemiparesis. The experimental group (n = 16) received robot-assisted UL training and BoNT treatment. The control group (n=16) received conventional treatment combined with BoNT treatment. Training protocols lasted for five weeks (45 min/session, two sessions/week). Before and after rehabilitation, a blinded rater evaluated patients. The primary outcome was the Modified Ashworth Scale (MAS). Secondary outcomes were the Fugl-Meyer Assessment Scale (FMA) and the Medical Research Council Scale (MRC). The electromyographic activity of 5 UL muscles during the “hand-to-mouth” task was explored in the experimental group and 14 healthy age-matched controls using a surface Electromyography (EMGs). Results: No significant between-group differences on the MAS and FMA were measured. The experimental group reported significantly greater improvements on UL muscle strength (p=0.004), shoulder abduction (p=0.039), extra-rotation (p=0.019) and elbow flexion (p=0.043) than the control group. In the experimental group, muscle strength changes were significantly correlated with FMA changes (r=0,49, p=0.05). EMGs data in the experimental group showed changes in the proximal muscles activity. Conclusions: The combination of Robot-assisted UL training and Botulinum toxin treatment is a promising therapeutic synergism in chronic stroke patients with upper limb spasticity. The instrumental assessment of muscle activity may identify specific UL impairments and suggest specific rehabilitation strategies.